Diffuse steatonecrosis - presenting as an obscure abdominal mass - a diagnostic dilemma - Kumar, Binay; Chachra, Upasna; Bhuvan, . (International Journal of Research in Medical Sciences, 2017)
Diffuse steatonecrosis secondary to acute / gangrenous pancreatitis presenting as vague abdominal mass is difficult to diagnose and requires special method / techniques for demonstration of fatty acid crystalloids. We report a case of acute abdomen with palpable lump. On emergency exploratory laprotomy a large thick jumbled up omental mass was revealed adhered to parietal wall along with complete pancreatic necrosis. Biopsy show diffuse fat necrosis of pericolic fat, omentum / mesentry with involvement of gut submucosa and birefringent saponified fatty acid crystalloids were demonstrated. Steatonecrosis may cause diagnostic dilemma and should be considered as differential diagnosis in appropriate clinical setting.